Impact of lesson study on mathematics anxiety and mathematics achievement of Malaysian foundation programme students - Hosseinali Gholami; Ahmad Fauzi Mohd Ayub; Aida Suraya Md Yunus; Nurzatulshima Kamarudin (Institute of Advanced Engineering and Science, 2021)
Based on many researches, there is negative relationship between mathematics anxiety and achievement. However, there is no study about mathematics anxiety and achievement in Malaysian foundation centers. This research studied the impact of Lesson Study (LS) on mathematics anxiety and achievement of students in a Malaysian university. A total of eight lecturers were involved in planning the LS which was experimented on 44 students as experimental group, while 42 others were in the control group. In the experimental group, students solved problems individually and in teams in a student-centered approach. For the control group, students were taught using the conventional method. Mathematics anxiety was measured using the Mathematics Anxiety Scale-Revised (MAS-R). A mathematics test was used to measure the students’ ability in problem solving. The data was analyzed using t-test, ANOVA and MANOVA. The results showed that there is a significant difference between the means of the experimental and control groups in mathematics anxiety and achievement scores. However, there is no statistically significant interaction between the effects of educational method and gender on both mathematics anxiety and achievement. LS was found to be a suitable method to increasing the student’s ability in problem solving and reducing their anxiety.